1996
DOI: 10.1111/j.1600-0536.1996.tb02416.x
|View full text |Cite
|
Sign up to set email alerts
|

Different pathways in irritant contact eczema?

Abstract: The epidermal response to 2 different irritants, nonanoic acid (NAA) and sodium lauryl sulfate (SLS), was investigated with 2 different methods. NAA 80% and SLS 4% were applied under occlusion for up to 24 h. Elemental changes were determined in cryosections by x-ray microanalysis. Compared to unexposed skin a significantly higher sodium/potassium ratio was found after 6 h in NAA-exposed skin and a lower ratio in SLS-exposed. At 24 h both substances had induced similar changes, compatible with a cell injury. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The disruption of the skin barrier leads to release of preformed IL-1 α [18], which represents an initial step in the inflammatory cascade of ICD. Numerous in vitro studies have also shown that various irritants induce IL-1 α expression in keratinocytes [5, 6, 1922]. Activation of IL-1 α is subsequently thought to stimulate further production of proinflammatory cytokines and chemokines such as IL-1 β , TNF- α , IL-6, and CXCL8 (IL-8) by surrounding epidermal and dermal cells [23, 24].…”
Section: Pathophysiology Of Irritant Contact Dermatitismentioning
confidence: 99%
See 1 more Smart Citation
“…The disruption of the skin barrier leads to release of preformed IL-1 α [18], which represents an initial step in the inflammatory cascade of ICD. Numerous in vitro studies have also shown that various irritants induce IL-1 α expression in keratinocytes [5, 6, 1922]. Activation of IL-1 α is subsequently thought to stimulate further production of proinflammatory cytokines and chemokines such as IL-1 β , TNF- α , IL-6, and CXCL8 (IL-8) by surrounding epidermal and dermal cells [23, 24].…”
Section: Pathophysiology Of Irritant Contact Dermatitismentioning
confidence: 99%
“…Other cytokines and factors that have been implicated in the pathogenesis of ICD and which are also produced by keratinocytes include vascular endothelial growth factor (VEGF) [21, 39, 40] and IL-6 [19, 27, 39]. VEGF which is mainly secreted by keratinocytes is a potent mediator of angiogenesis that stimulates the migration and proliferation of endothelial cells, facilitates vascular permeability, and induces the expression of adhesion molecules ICAM-1 and VCAM-1 on endothelial cells [39].…”
Section: Pathophysiology Of Irritant Contact Dermatitismentioning
confidence: 99%
“…Various studies on cytokine production in response to irritants have shown production of TNFa, IL-8, IL-1b, IL-1a and IL-8 (23). The cytokines that give Langerhans cells an immunostimulatory morphology, namely GMCSF, IL-1 and TNFa, are also produced by irritants (24)(25)(26).…”
Section: Tnfa Irritancy and Allergymentioning
confidence: 99%
“…Since acute inflammatory response in epidermis depends on the chemical structure of the applied irritant. 19 three structurally different irritants, sodium lauryl sulfate (SLS), NaOH (sodium hydroxide) and benzalkonium chloride (BKC), were used as model irritants. To date, most published studies have investigated a small number of genes and/or SNPs and focused on clinical ICD.…”
Section: Introductionmentioning
confidence: 99%